USING PARALLEL SERVICE TECHNIQUES TO CONTROL SYSTEM LOAD - Abdullaev, Eldor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
At the moment, remote service systems are being used more frequently to implement work and study activities. This calls for the accomplishment of activities including enhancing the fundamentals of remote systems using information and communication technologies, which are the system's constituents, picking the appropriate categories of services, and picking acceptable system-related hardware. Choosing appropriate service delivery techniques for distance education systems is a topic that is discussed in this article. Additionally, it was discovered that forming the system component using techniques appropriate for the service task could improve the service's quality and cut down on the amount of time needed to provide it